Hemoptysis caused by bronchial artery‐pulmonary artery fistula complicated with Dieulafoy disease: A case report - Chongqing Lv; Tao Feng; Shishou Wang; Chen Lin (Respirology Case Reports)
Abstract Bronchial artery‐pulmonary artery fistula (BPF) is a rare vascular malformation of the bronchial arteries, associated with congenital heart disease, pulmonary hypertension, or pulmonary infections. It typically presents in adulthood and has a low incidence. Another rare vascular anomaly, bronchial Dieulafoy disease (BDD), is characterized by an abnormally developed artery within the submucosa of the bronchial tree. This condition is thought to arise from a combination of congenital dysplasia and chronic airway inflammation or injury. Both BPF and BDD are uncommon causes of hemoptysis, and their simultaneous occurrence is exceptionally rare. This report discusses a case of BPF complicated by BDD in a patient who presented with recurrent hemoptysis. The diagnosis was established through bronchial artery angiography, bronchoscopy, and surgical pathology. By examining the clinical features, imaging findings, and diagnostic criteria of these conditions, this case report aims to enhance clinicians' understanding of cryptogenic hemoptysis and provide valuable insights for clinical practice.